Turismo rural e sustentabilidade: uma análise de múltiplos casos no estado de Roraima - Bezerra, Suelen Santos (2017)
Tourism has been diffused in many parts of the world by being seen as an alternative to supplementing income or as a business opportunity. The inclusion of this activity to improve the family income and, at the same time, to take advantage of the space of its properties has been increasing the practice of rural tourism in small and medium properties in the rural area. The environmental issue, currently in the rural tourism scenario, is extremely important as the maintenance of environmental resources is part of the rural environment that visitors seek, making environmental conservation one of the key strategies for the diffusion of rural tourism in the State. With the main objective of realizing a panorama of the rural tourism in Roraima and its implications with the environment, a research was carried out in eight properties that practice the Rural Tourism activity in the State of Roraima. In order to do so, we sought to analyze the potential of the enterprises that promote Rural Tourism in Roraima, to map the tourist attractions that drive rural tourism in the State, and to analyze the interrelation between rural tourism and sustainability in the environmental scope. The research is exploratory and descriptive, with a qualitative approach. Data were collected through interviews with semi - structured questions, applied to owners and managers of two projects of Rural Tourism in the State; also, a bibliographic research and direct observation were done, to cross the information obtained. It was observed that there is only one property that practices rural tourism, as it offers tours to horses, trails, typical foods of the rural environment and the concern to keep the familiar roots in the place, as well as agricultural and agricultural activities. In the other researched properties, some were not working at the moment of the research and the others did not characterize their activities in the modality of rural tourism. It was concluded that rural tourism in Roraima is incipient, even though it has great potential. Regarding the environmental dimension of sustainability, it was verified that of the eight properties observed, only one of them practices rural tourism, and the rest of the properties have potential, but the conclusion is that they produce tourism in the rural space. However, in tourism, the impacts must be taken into account, given its extreme importance with the protection of the environment.